Improvement of Mouth Functional Disability in Systemic Sclerosis Patients over One Year in a Trial of Fat Transplantation versus Adipose-Derived Stromal Cells - Maria Giuseppina Onesti; Paolo Fioramonti; Sara Carella; Pasquale Fino; Cinzia Marchese; Nicolò Scuderi (Stem Cells International)
Background. Systemic sclerosis (SSc) is a multisystem disease characterized by cutaneous and visceral fibrosis. Face and mouth changes include telangiectasia, sicca syndrome, and thinning and reduction of mouth width (microcheilia) and opening (microstomia). We applied autologous fat transplantation compared with autologous adipose-derived stromal cells (ADSCs) injection to evaluate the clinical improvement of mouth opening. Methods. From February to May 2013 ten consecutive SSc patients were enrolled from the outpatient clinic of Plastic Surgery Department of Sapienza University of Rome. Patients were divided into two groups as follows: 5 patients were treated with fat transplantation and 5 patients received infiltration of ADSCs produced by cell factory of our institution. To value mouth opening, we use the Italian version of Mouth Handicap in Systemic Sclerosis Scale (IvMHISS). Mouth opening was assessed in centimetres (Maximal Mouth Opening, MMO). In order to evaluate compliance and physician and patient satisfaction, we employed a Questionnaire of Satisfaction and the Visual Analogic Scale (VAS) performed before starting study and 1 year after the last treatment. Results and Conclusion. We noticed that both procedures obtained significant results but neither one emerged as a first-choice technique. The present clinical experimentation should be regarded as a starting point for further experimental research and clinical trials.